Can Green Hydrogen Production Be Economically Viable under Current Market Conditions - David Jure Jovan; Gregor Dolanc (Energies, 2020)
This paper discusses the potential of green hydrogen production in a case study of a Slovenian hydro power plant. To assess the feasibility and eligibility of hydrogen production at the power plant, we present an overview of current hydrogen prices and the costs of the power-to-gas system for green hydrogen production. After defining the production cost for hydrogen at the case study hydro power plant, we elaborate on the profitability of hydrogen production over electricity. As hydrogen can be used as a sustainable energy vector in industry, heating, mobility, and the electro energetic sectors, we discuss the current competitiveness of hydrogen in the heating and transport sectors. Considering the current prices of different fuels, it is shown that hydrogen can be competitive in the transport sector if it is unencumbered by various environmental taxes. The second part of the paper deals with hydrogen production in the context of secondary control ancillary service provided by a case study power plant. Namely, hydrogen can be produced during the time period when there is no demand for extra electric power within a secondary control ancillary service, and thus the economics of power plant operation can be improved.